Axon guidance pathways and the control of gene expression. Issue 4 (5th January 2018) - Russell, Samantha A.; Bashaw, Greg J.
Abstract : Axons need to be properly guided to their targets to form synaptic connections, and this requires interactions between highly conserved extracellular and transmembrane ligands and their cell surface receptors. The majority of studies on axon guidance signaling pathways have focused on the role of these pathways in rearranging the local cytoskeleton and plasma membrane in growth cones and axons. However, a smaller body of work has demonstrated that axon guidance signaling pathways also control gene expression via local translation and transcription. Recent studies on axon guidance ligands and receptors have begun to uncover the requirements for these alternative mechanisms in processes required for neural circuit formation: axon guidance, synaptogenesis, and cell migration. Understanding the mechanisms by which axon guidance signaling regulates local translation and transcription will create a more complete picture of neural circuit formation, and they may be applied more broadly to other tissues where axon guidance ligands and receptors are required for morphogenesis. Developmental Dynamics 247:571–580, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Axon receptors regulate gene expression.